The potential of composite flour (sago and fish) as a source of raw materials for frozen food processing - Sumarto Sumarto; Suparmi Suparmi; Diharmi Andarini; Karnila Rahman; Hidayat Taufik (BIO Web of Conferences)
A mixture of sago flour and fish flour (Ilisha elongata) can be used as a composite flour source of raw material for food processing production of functional value. The research aimed to determine the characteristics of composite flour from sago and bang fish flour with concentration. The experimental research method processed composite flour from sago flour and fish flour with varying additions of fish flour 1%, 5%, and 10% of the total sago flour. The composite flour was subjected to a gelatinization process, a cooking method that involves heating the flour in water to form a gel to obtain its characteristics. The result showed that the processing of composite flour with fish flour affects the moisture content, protein, fat, ash, carbohydrates, mineral content, and profile of the number of essential and non-essential amino acids of composite flour. The best concentration of composite flour was 10%, with a high protein of 6.39 and calcium of 2869 mg/kg. Methionine and glutamate Methionine and glutamate are the highest amino acids, and the degree of gelatinization is 93.95%. Composite flour, with a concentration of 10%, has much potential for applied frozen food products (nuggets and fish balls).